(untitled) (Terr@ Plural, 2022)
This paper aims to provide a theoretical reference for studies on the paleoecology of benthic marine fauna to better understand the terms used in recent studies, or not, on the subject. Through a literature search listing the most relevant works on the subject, it was concluded that the authors use the terms paleocommunities and guilds for the classification of fauna, but nowadays concepts such as functional groups and ecological niches have been used as synonyms. Thus, many older papers can finally be reviewed from a different point of view, providing more detail, and answering open questions. Furthermore, it was observed that there is little discussion on the use of paleoecological concepts to elucidate the life history of fossil assemblages, especially from the Paraná Basin.